2020
DOI: 10.3348/kjr.2019.0010
|View full text |Cite
|
Sign up to set email alerts
|

Using 2-mSv Appendiceal CT in Usual Practice for Adolescents and Young Adults: Willingness Survey of 579 Radiologists, Emergency Physicians, and Surgeons from 20 Hospitals

Abstract: Objective: To survey care providers' willingness to use 2-mSv computed tomography (CT) in their usual practice for adolescents and young adults with suspected appendicitis. Materials and Methods: An ethical committee approved this prospective study. We introduced 2-mSv CT in 20 hospitals through a pragmatic clinical trial. At the final phase of the trial, we invited 698 potentially-involved care providers in the survey regarding their willingness to use 2-mSv CT. Multivariable logistic regression analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…First, although the appendix is well visualized in more than 85% of patients even on 2-mSv CT, as shown in previous studies [ 31 32 ], appendiceal visualization is slightly hampered by the use of 2-mSv CT instead of CDCT. This is in line with practitioners’ concerns regarding the use of 2-mSv CT [ 12 ]. Second, appendiceal nonvisualization rarely leads to undesirable outcomes, even with the use of 2-mSv CT instead of CDCT.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…First, although the appendix is well visualized in more than 85% of patients even on 2-mSv CT, as shown in previous studies [ 31 32 ], appendiceal visualization is slightly hampered by the use of 2-mSv CT instead of CDCT. This is in line with practitioners’ concerns regarding the use of 2-mSv CT [ 12 ]. Second, appendiceal nonvisualization rarely leads to undesirable outcomes, even with the use of 2-mSv CT instead of CDCT.…”
Section: Discussionsupporting
confidence: 75%
“…However, when the radiation dose is as low as 2 mSv, radiologists may be uncertain as to whether appendiceal nonvisualization is attributable to the small size of an uninflamed appendix or to the compromised image quality hindering the detection of an enlarged appendix with inflammation. Some practitioners are concerned that appendiceal nonvisualization is more common with the use of low-dose CT instead of conventional-dose CT (CDCT), which may lead to undesirable clinical or diagnostic outcomes such as negative appendectomy, perforated appendicitis, or delay in patient management [ 12 ]. In this study, we compared appendiceal visualization on 2-mSv CT vs. CDCT in adolescents and young adults with suspected appendicitis and analyzed undesirable clinical and diagnostic outcomes that followed appendiceal nonvisualization.…”
Section: Introductionmentioning
confidence: 99%
“…As exploration of the factors associated with clinical application of reduced CT dose was beyond the scope of our study, we have not acquired data in this study to compare to a recent study. A recent clinical trial reported that the reading time and preferences of the reader, referring physicians, and hospital system could affect the clinical application of reduced radiation dose CT (43). Further practical efforts are required to implement reduced CT radiation dose in usual practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the adoption of LDCT is disappointingly slow. A survey [ 8 ] in 2016 showed that care providers were still concerned that the low image quality with LDCT may lead to incorrect diagnoses. It is disappointing that some care providers are still unaware of or disregard previous study results showing that LDCT is comparable to conventional dose CT (CDCT).…”
Section: Introductionmentioning
confidence: 99%